Recasting the Bureau of Customs as a Developmental Agency - Mendoza, Ronald U (Archīum Ateneo, 2014)
This paper estimates that 40 centavos out of every 1 peso in potential revenues is lost to corruption in the Philippine Bureau of Customs. Ending the “corruption finance” propagated through tax leakages in the BOC could be good in and of itself for the country, but international evidence and experience suggest that our customs agency has the potential to become much more relevant to the broader economic development agenda. It could very well be the vanguard of trade facilitation for the country, by simplifying and harmonizing international trade procedures, and thus also lowering the costs and the “friction” of moving goods across our borders. This paper reviews some of the governance issues surrounding customs administration; and it also discusses the possible developmental role of this agency.